2020
DOI: 10.1073/pnas.2007935117
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of USF2 in refractory rheumatoid arthritis and its regulation of proinflammatory cytokines in Th17 cells

Abstract: IL-17–producing Th17 cells are implicated in the pathogenesis of rheumatoid arthritis (RA) and TNF-α, a proinflammatory cytokine in the rheumatoid joint, facilitates Th17 differentiation. Anti-TNF therapy ameliorates disease in many patients with rheumatoid arthritis (RA). However, a significant proportion of patients do not respond to this therapy. The impact of anti-TNF therapy on Th17 responses in RA is not well understood. We conducted high-throughput gene expression analysis of Th17-enriched CCR6+CXCR3−CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 72 publications
(87 reference statements)
0
19
0
Order By: Relevance
“…Among alternative possibilities, TNF-α makes a contribution towards the differentiation of IL-17A producing Th17 cells [ 15 ] and subsequent synergy with IL-17A further increases the potency of TNF-α [ 8 ]. Pathogenic Th17 cells are a feature of RA, distinguished by a pro-inflammatory gene signature that includes elevated TNF transcript in non-responders [ 27 ] and is sustained by USF2 signalling pathways [ 28 ]. Importantly, TNF-α production by Th17 lineage cells increases as the cells trans-differentiate from classic Th17 cells, through IL-17A + IFNγ + ex-Th17 intermediaries, towards non-classical IFNγ + Th1 cell phenotypes, which concomitantly acquire a more pathogenic phenotype [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among alternative possibilities, TNF-α makes a contribution towards the differentiation of IL-17A producing Th17 cells [ 15 ] and subsequent synergy with IL-17A further increases the potency of TNF-α [ 8 ]. Pathogenic Th17 cells are a feature of RA, distinguished by a pro-inflammatory gene signature that includes elevated TNF transcript in non-responders [ 27 ] and is sustained by USF2 signalling pathways [ 28 ]. Importantly, TNF-α production by Th17 lineage cells increases as the cells trans-differentiate from classic Th17 cells, through IL-17A + IFNγ + ex-Th17 intermediaries, towards non-classical IFNγ + Th1 cell phenotypes, which concomitantly acquire a more pathogenic phenotype [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the increased concentration of IL-17A and/or Th17 in inflamed joints and blood of the patients suffering RA. It was recently shown a relation of IL-17A concentrations with the disease activity or joint damage [54,55]. Recent understanding of the etiopathogenesis of RA emphasized the role of the cytokine network in the initialization and development of the illness, which has bought a novel class of drugs for RA directly targeting cytokines [56].…”
Section: Discussionmentioning
confidence: 99%
“…4 ). 36 , 37 Inflammation associated cytokines or other soluble factors in patient serum, including IL-2, IL-6, IL-17A, IL-21 TNF-α, IFN-γ, sCD25, IL-4, IL-12, TGF-β, and CXCL13, were determined by ELISA kits (MultiSciences, Hangzhou, China), following instructions from the manufacturer.…”
Section: Methodsmentioning
confidence: 99%